COMPARATIVE ANALYSIS OF TRADING SYSTEMS PERFORMANCES WITH RESPECT TO TRANSACTION COSTS (Part II) - JANAHMADOV, E.A. (Herald of Azerbaijan Engineering Academy, 2021)
The purpose of this paper is to compare and analyze the performance of trading rules applied to the underlying and derivative products. Three different trading market indictors were chosen from the range of trading rules according to their performance relatively to Dow Jones Industrial Average. On the basis of these technical indicators the automated trading systems were developed and then applied to the underlying instrument such Dow Jones Industrial Average. The performances of trading systems and profit/loss indexes were compared and analyzed. The results are compared with “buy-and-hold” strategy and performance of underlying security. The results of the research intend to show the effect of the transactions costs on the performance of trading systems and optimal could be applied to invest into underlying or derivatives of underlying.